Substance Users’ Perspectives on Helpful and Unhelpful Confrontation: Implications for Recovery - Polcin, Douglas (2012)
Substance users commonly face confrontations about their use from family, friends, peers, and professionals. Yet confrontation is controversial and not well understood. To better understand the effects of confrontation we conducted qualitative interviews with 38 substance users (82% male and 79% white) about their experiences of being confronted. Confrontation was defined as warnings about potential harm related to substance use. Results from coded transcripts indicated that helpful confrontations were those that were perceived as legitimate, offered hope and practical support, and were delivered by persons who were trusted and respected. Unhelpful confrontations were those that were perceived as hypocritical, overtly hostile, or occurring within embattled relationships. Experiences of directive, persistent confrontation varied. Limitations of the study include a small and relatively high functioning sample. We conclude that contextual factors are important in determining how confrontation is experienced. Larger studies with more diverse samples are warranted.